2019
DOI: 10.1002/lsm.23066
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fractional CO2 laser in the treatment of genitourinary syndrome of menopause in Latin‐American Population: First Peruvian experience

Abstract: Objective This PUBA study aimed to assess the efficacy of fractional CO2 laser in the treatment of genitourinary syndrome of menopause (GSM). Methods GSM symptoms were assessed before, 1 month after the first session and 1 month after the third session of laser (3 sessions with a 30 days interval between them) in 60 women (median, interquartile range: 55, 49–69). Subjective (visual analog scale) and objective (Vaginal Health Index, VHIS; Vaginal Maturity Index/Frost Index; Spanish Overactive Bladder Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 33 publications
3
53
0
Order By: Relevance
“…QoL improved significantly in three studies . Urinary incontinence scores also improved significantly, and results were maintained for at least 3 months after treatment …”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…QoL improved significantly in three studies . Urinary incontinence scores also improved significantly, and results were maintained for at least 3 months after treatment …”
Section: Discussionmentioning
confidence: 84%
“…However, most stated three laser treatments led to a superior score and sustained results. Four studies used the VMV . Three of these studies reported a significant increase in maturation value, while the fourth reported no difference .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations